A new method of determining factors affecting arterial blood pressure indices among young adults with Sickle Cell Anaemia and Haemoglobin AA in Nigeria - Jamiu Saka, Adisa; Adebukola Akintunde, Muhammed; Adedayo Adeleke, Kazeem; Abiola Asafa, Muritala; Adewale Osuolale, Kazeem; Bolale Adeoye, Bashirat; Silvio de Sousa Bueno Filho, Julio (Brazilian Journal of Biometrics, 2026)
Sickle Cell Anaemia (SCA) is a genetic blood disorder caused by a mutation in the haemoglobin gene, leading to the production of abnormal haemoglobin known as haemoglobin S. This abnormal haemoglobin causes red blood cells to become rigid, sticky, and shaped like a crescent or sickle, which obstructs blood flow and leads to various complications such as pain, infections, and potential damage to nerves and organs (kidneys, liver and spleen). This research utilizes a two-level factorial experiment to evaluate the impact of four major factors (Age, Sex, Genotype, and Rhythm) on six distinct blood pressure (BP) indices: Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), Pulse Rate (PR), Pulse Pressure (PP), Mean Arterial Pressure (MAP), and Rate Pressure Product (RPP). The experimental units consist of young adults with Sickle Cell Anaemia (SCA) and Haemoglobin AA (HbAA). The results of the analysis indicate that Age and Genotype are the major significant factors affecting blood pressure (BP) indices. Meanwhile, Pulse Pressure (PP) appears to be more sensitive to the aforementioned factors when compared to SBP or DBP. Also, the interaction effects between Age and Genotype, and between Age and Sex demonstrate clinical relevance. Importantly, these results highlight the importance of early detection of abnormal cardiovascular symptoms and open ways for further heart disease diagnostic tests and treatments in young adults. It is also worthwhile to note that Pulse Pressure (PP) provides a more comprehensive measure for abnormal cardiovascular detection within young adults.